2022
DOI: 10.1007/s13399-022-02935-x
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of bagasse alkali lignin to water-soluble derivatives through chemical modification

Abstract: Black liquor is the by-product of the pulping process where the lignin, hemicellulose, and extractive materials are separated from wood to produce paper pulp. As one of the primary lignin sources, black liquor is considered an important energy source from biomass to produce biofuels and value-added chemicals. However, soda alkaline lignin has limited industrial applications due to its insolubility in water and lack of reactivity. Therefore, chemical modification is essential to enhance its industrial applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The results of TGA studies revealed that aminated lignin had lower thermal stablitiy than kraft lignin . On the other hand, the introduction of funtional groups, like sulfonates that enhanced intermolecular interactions of lignin molecules, should improve the thermal stability of lignin . Jiao et al compared the thermal stability of aminated lignin with different functional groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of TGA studies revealed that aminated lignin had lower thermal stablitiy than kraft lignin . On the other hand, the introduction of funtional groups, like sulfonates that enhanced intermolecular interactions of lignin molecules, should improve the thermal stability of lignin . Jiao et al compared the thermal stability of aminated lignin with different functional groups.…”
Section: Resultsmentioning
confidence: 99%
“…29 On the other hand, the introduction of funtional groups, like sulfonates that enhanced intermolecular interactions of lignin molecules, should improve the thermal stability of lignin. 30 Jiao et al 31 compared the thermal stability of aminated lignin with different functional groups. The results revealed that the fuctional groups with branch structure resulted in modified lignin with lower thermal stability.…”
Section: Synthesis Of Aminoalkyl Lignin With Different Aliphatic Chainmentioning
confidence: 99%
“…In surfactant chemistry, the modulation of physicochemical properties is often the goal, whereas other approaches may seek to enable or improve the use in polymeric materials. , Concerning the latter, increasing the reactivity of lignin is frequently the goal, which can be achieved by alkylation (epoxy resins), allylation or alkynylation, , phenolation (phenolic resins), or carboxylation (polyesters) . Water-solubility for the use as surfactants is usually facilitated by adding ionizable moieties, e.g., by sulfonation, sulfomethylation, or carboxylation . The opposite effect, i.e., hydrophobization and lipophilization, can be achieved by silylation or esterification with fatty acids. , Such treatments have also been demonstrated to improve compatibility with olefin thermoplastics, e.g., polyethylene or polypropylene. ,, It has also been demonstrated that Kraft lignin esterified with fatty acids was soluble in nonpolar solvents .…”
Section: Introductionmentioning
confidence: 99%
“…For example, researchers prepared sulfomethylated lignin by inserting metabisulfite into the sulfonation process with the help of nitric acid and formaldehyde, increasing the sulfonation levels to 2.05 meq g −1 [18] . From the viewpoint of molecular weight and degree of sulfonation, Hui [19] evaluated different sulfonation methods, including high‐temperature sulfonation, sulfomethylation, butane sulfonolactone sulfonation, and sodium borohydride treatment of butane sulfonolactone sulfonation products [20] . A sulfonate group was added, and it was found that not only did it lighten the color of lignin for more industrial uses, but it also kept its molecular weight and even increased it in some ways, making the original lignin more stable at high temperatures [21] …”
Section: Introductionmentioning
confidence: 99%
“…[18] From the viewpoint of molecular weight and degree of sulfonation, Hui [19] evaluated different sulfonation methods, including high-temperature sulfonation, sulfomethylation, butane sulfonolactone sulfonation, and sodium borohydride treatment of butane sulfonolactone sulfonation products. [20] A sulfonate group was added, and it was found that not only did it lighten the color of lignin for more industrial uses, but it also kept its molecular weight and even increased it in some ways, making the original lignin more stable at high temperatures. [21] As lignosulfonates are dissolved in water, the hydrophobic skeleton of C 3 -C 6 forms a spherical structure.…”
Section: Introductionmentioning
confidence: 99%